Transgenic rice as bioreactor for production of the Candida antarctica lipase B. Issue 7 (23rd May 2014) - Yang, Ying; Wang, Dongfang; Zhang, Xianwen; Fang, Jun; Shen, Zhicheng; Lin, Chaoyang
Summary Candida antarctica lipase B (CALB) is a versatile biocatalyst used for a wide range of biotransformation. Methods for low cost production of this enzyme are highly desirable. Here, we report a mass production method of CALB using transgenic rice seeds as the bioreactor. The transgenic rice transformed with the CALB gene under the control of the promoter of the rice seed storage protein GT1 was found to have accumulated a large quantity of CALB in seeds. The transgenic line with the highest lipolytic activity reached to 85 units per gram of dry seeds. One unit is defined as the amount of lipase necessary to liberate 1 μmol p‐nitrophenol from p‐nitrophenyl butyrate in 1 min. The rice recombinant lipase (rOsCALB) from this line represents 40% of the total soluble proteins in the crude seed extracts. The enzyme purified from the rice seeds had an optimal temperature of 40 °C, and optimal pH of 8.5, similar to that of the fermentation products. Test of its conversion ability as a biocatalyst for biodiesel production suggested that rOsCALB is functionally identical to the fermentation products in its industrial application.